Insider Forces and Wage Determination. - Nickell, S; Wadhwani, S (CEPR, 1989)
This paper attempts to assess the relative importance of firm-specific factors (i.e., insider forces) in wage determination. Using firm-level data on 219 UK companies over the period 1974-82, it finds that a 1% rise in a firm's prices or productivity relative to the aggregate economy leads to a rise in relative wages of 0.1-0.2%. As a corollary to this, outside factors such as the aggregate wage and the unemployment rate also play an important role. There is evidence for hysteresis effects based on insider forces, but these are inversely related to the extent to which firms take national agreements into account.